Integration of investment strategies in the system of strategic planning of territorial development - O. V. Kozhevina (Управление)
The issues of legal regulation of investment activity at the level of the Federation entities of the Russian Federation have been considered. The purpose of the research is the study of strategic documents in the field of investment activities of the Federation entities of the Russian Federation and the regulatory framework. The object of the research is the mechanism of strategic planning of investment development of territories. An empirical study of the implementation of investment processes in Russian regions has showed, that legal regulation is heterogeneous, but in general, well presented and allows improving the investment climate and encouraging investment, as well as to some extent influencing the economic security of the regions. The experience of the functioning of specialized organizations to attract investment and work with investors, the organization of public-private partnership at the regional level has been studied. The algorithm of approval of investment projects of territorial development has been presented.On the example of a large Russian region - the Altai Territory - the provisions and principles of the investment declaration of the subject, such as equality of the subjects of entrepreneurial and investment activities, involvement of subjects of entrepreneurial and investment activities in the investment process, transparency (openness) of information, the use of best practices of work with investors have been considered. A set of internal measures and instruments for the implementation of an effective investment policy at the regional level has been determined. Attention has been paid also to the relevant issue of concluding concession agreements as a way to develop territories and implement infrastructure projects. Internal measures have been proposed to increase the investment attractiveness of the Russian regions, in particular, are necessary the transformation of the business climate, increasing the responsibility of regional executive authorities for the investment development of territories and creating a favorable investment climate, ensuring the availability of long-term financing sources for investment projects, the development of venture financing and crowdfunding.